Wychowanie - droga do wolności czy do zniewolenia : ryzyko wychowawcze - Biernacki, Marek (Education to Freedom Or Constraint : the Risk of Education, 2006)
Contemporary Polish and foreigner educationists, educators and scientists more often and louder speak about crisis in upbringing and education: the triumph of technology over culture, the crisis of intelligence and elite incapable of changes. The end of work was announced, and what follows - decline of the scientific era. The decline of identity also came, of the stable reference system, of authorities and of models to follow by the youth. The importance of the problem is great because it regards young people (also students) who rebuild the society and who will be deciding about the future.On the authorities of the speeches and works of John Paul II, L. Giussani - the priest and the founder of the Movement Comunione e Liberazione and professor Salsa - rector of the University of Madrid, I am trying to show the way out from the existing situation. Why the Risk of Education? Because education should introduce the learner to the entire reality. The educator should have at least general hypothesis explaining everything, and should also communicate their own way of relating to reality. This work of educator is marked by the risk because it is addressed to the freedom of the learner who can either accept or reject it. In short, education is communication of the particular past being experienced at the present and being submitted to some criticism.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1117, s. 11-16